Integrating Decision Support Systems in Agroindustrial Business Development: A Case Study of Jackfruit Chips Enterprises in Indonesia - Nabil Abror, Alfin; Eka Ardhi Pratama, Fredy; Eka Putra, Dhanang (CV. SPDFHarmony, 2025)
Background: Agroindustrial enterprises play a vital role in strengthening rural economies and creating value-added agricultural products. In Indonesia, small and medium enterprises (SMEs) producing processed fruit snacks, such as jackfruit chips, face persistent challenges related to resource management, production efficiency, and fluctuating market demand. Addressing these issues requires systematic tools for evaluation and decision-making. Aims: This study aims to assess the business feasibility of UD Matrix Jaya, an agroindustrial enterprise producing jackfruit chips, and to propose strategic development recommendations through the integration of a Decision Support System (DSS). Methods: A mixed-method descriptive design was employed, combining financial and non-financial feasibility analyses. Primary data were collected through interviews and structured questionnaires with business owners, while secondary data were obtained from company records. The DSS-UMKM v.2.0 framework was utilized to evaluate six dimensions: legal, marketing, production, management and human resources, environmental, and financial aspects. Results: Findings reveal that legal, production, and environmental aspects achieved a moderate level of feasibility, while marketing scored high. Conversely, management and human resources were rated low. Financial analysis demonstrated viability with positive Net Present Value (NPV), Internal Rate of Return (IRR) exceeding the discount rate, and a feasible Payback Period (PP). Overall, the DSS evaluation confirmed that the enterprise is suitable for further development. Conclusion: The integration of DSS provides a structured mechanism for SMEs to overcome multidimensional challenges in agroindustry. For UD Matrix Jaya, strategic priorities include strengthening managerial capacity, enhancing workforce quality, and optimizing production processes alongside marketing innovation. These measures are expected to improve competitiveness, ensure sustainability, and serve as a model for similar enterprises in emerging economies. By bridging technological decision-making tools with agroindustrial development, this research contributes to advancing sustainable agribusiness practices and supports policy directions toward empowering rural-based SMEs in Indonesia.